Critical Design Factors on Performance of Car Jack Lifting Operations - Dzul Hafez Yacob; S. Sarip; M. A. Suhot; M. Z. Hassan; S. A. Aziz; M. Y. Daud; N. A. Bani; M. N. Muhtazaruddin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Car jack is an equipped accessory package in every units of car sold to customer that used to uplift the cars while replacing tires during an emergency or repair. The automotive manufacturers are actively conducting their Product Improvement Campaign and the objective of the campaign is to improve the quality of product sold to the customers. The current jack design has a possibility of failure during its operations. The customer satisfaction point of view will be converted to engineering characteristic to acquire the concept of design and input into new design proposal and at the same time eliminate the possibility of failure of the current design. The research is conducted to improve the current jack design on its performance in lifting operations. The scope of research is to identify the critical zone in jack design structure that possibly causing the failure during its operations. To optimize the existing design, it is proposed some modification on the jack structure with a minimum weight increment but improve the design structural strength. The failure root cause analysis, reliability test and Design Failure Mode and Effect Analysis have been used to identify the specific critical area in the structure and resolve them by proposing the new improved jack design. The current car jack sample in market is used as an industrial sample for design analysis to find the target area for further improvement. From the analysis, we can know the critical design factors in the current car jack design and the required design improvement to enhance its performance in lifting operations.